Gerakan Politik S.M. Kartosoewirjo (DI/TII 1949 – 1962) - WAHYU IRWANSYAH TAMBUNAN (Universitas Sumatera Utara, 2014)
Political movement is a social movement in politics. Political movement is more than a movement that has the purpose of achieving political power. This is a study about political movement of Kartosoewirjo. Darul Islam and the Indonesian Islamic Army as a political move-ment. The focus discusses whether Darul Islam movement and the Indonesian Islamic Army led by S.M. Kartosoewirjo (1949 – 1962) was a political movement. The findings of this study among others, there are three things which explains that the Darul Islam / Indonesian Islamic Army is a political movement. First, the establishment of the movement of DI/TII as a form of disillusionment with the leadership of Soekarno; Second, the mobilization of resources is done in the movement of DI/TII; Third, the movement of DI/TII managed to cause political tensions with the Indonesian government. The method used is descriptive-qualitative method that is in-tended to describe an event in more detail.Keywords: Darul Islam, Indonesian Islamic Army, political movement.